Single-lined spectroscopic binary star candidates from a combination of the RAVE and Gaia DR2 surveys - Birko, Danijela; Zwitter, Tomaž; Grebel, Eva K.; Parker, Quentin A.; Kordopatis, Georges; Bland-Hawthorn, Joss; Freeman, Kenneth; Guiglion, Guillaume; Gibson, Brad K.; Navarro, Julio; Reid, Warren; Seabroke, G. M.; et al. (The astronomical journal, 2019)
The combination of the final version of the Radial Velocity Experiment (RAVE) spectroscopic survey data release 6 with radial velocities (RVs) and astrometry from Gaia DR2 allows us to identify and create a catalog of single-lined binary star candidates (SB1), their inferred orbital parameters, and to inspect possible double-lined binary stars (SB2). A probability function for the detection of RV variations is used for identifying SB1 candidates. The estimation of orbital parameters for main-sequence dwarfs is performed by matching the measured RVs with theoretical velocity curves sampling the orbital parameter space. The method is verified by studying a mock sample from the SB 9 catalog. Studying the boxiness and asymmetry of the spectral lines allows us to identify possible SB2 candidates, while matching their spectra to a synthetic library indicates probable properties of their components. From the RAVE catalog we select 37,664 stars with multiple RV measurements and identify 3838 stars as SB1 candidates. Joining Rave and Gaia DR2 yields 450,646 stars with RVs measured by both surveys and 27,716 of them turn out to be SB1 candidates, which is an increase by an order of magnitude over previous studies. For main-sequence dwarf candidates we calculate their most probable orbital parameters: orbital periods are not longer than a few years and primary components have masses similar to the solar mass. All our results are available in the electronic version.